2013
DOI: 10.1590/s1415-47572013000100008
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis of Zaprionus indianus and Zaprionus sepsoides (Diptera, Drosophilidae): cytochemical, structural and ultrastructural characterization

Abstract: Zaprionus indianus is a drosophilid native to the Afrotropical region that has colonized South America and exhibits a wide geographical distribution. In contrast, Z. sepsoides is restricted to certain African regions. The two species differ in the size of their testes, which are larger in Z. indianus than in Z. sepsoides. To better understand the biology and the degree of differentiation of these species, the current study evaluated spermatogenesis in males of different ages by conventional staining techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Most insect sperm bear two elongated mitochondrial derivatives along the flagellum 45 47 . In some insect species, the two mitochondrial derivatives in a single spermatozoon differ in ultrastructural features, such as their size and the material they contain 48 , 49 . In Drosophila , defects in the larger mitochondrial derivatives induce male sterility 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Most insect sperm bear two elongated mitochondrial derivatives along the flagellum 45 47 . In some insect species, the two mitochondrial derivatives in a single spermatozoon differ in ultrastructural features, such as their size and the material they contain 48 , 49 . In Drosophila , defects in the larger mitochondrial derivatives induce male sterility 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The germ cells continue spermatogenesis within the follicular cells, progressively forming spermatogonia, spermatocytes, spermatids, and spermatozoa defining the histological zones of growth, maturation, and transformation respectively ( Smith 1968 ). The distinct zones can be observed simultaneously during active spermatogenesis ( Rego et al 2013 ), but in emergent drones only the final stage may be observed histologically ( Snodgrass 1910 ). The mature spermatozoa are bundled together [forming spermatodesms ( Smith 1968 )] and rupture free from the follicular cell into the follicular lumen and progress towards vas efferens and common vas deferens.…”
mentioning
confidence: 99%
“…Cruz-Landim has also observed glycogen in the testicles of bees. 18,20
Figure 1. TEM micrographs of Zaprionus testes.
…”
Section: Resultsmentioning
confidence: 99%
“…Yellowing has also been observed in the sheaths of Z. indianus, Z. sepsoides and Z. spinipilus that were analyzed previously. 18,22,23 However, Z. vittiger was polymorphic for sheath color, which may be yellow or brownish purple. 23 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation